2018
DOI: 10.53369/rkxa7855
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Behavioral Biases on Investment Decision Making with Moderating Role of Financial Literacy

Abstract: The objective of this study is to examine the Impact of Overconfidence bias and Herding bias on Investment Decision Making with Moderating Role of Financial Literacy. The population was Investor, Employee and Graduate Student. A sample of 200 was selected using convenience technique. Data were collected through structure questionnaire adopted from different papers. Correlation and Regression analysis were performed to examine the result. The Results show that overconfidence bias and herding bias have a positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 2 publications
3
13
0
4
Order By: Relevance
“…Next, the seventh hypothesis (H7) is also confirmed and accepted, showing that overconfidence influences investor decision making with š›½-value was 0.228, with t-statistics value was 3.629 corresponding to p-value ā‰¤ 0.01. Related previous research also found that overconfident investors increase their investment ambitiously [84]. After that, the eighth hypothesis (H8) is also confirmed and accepted, showing that anchoring influences investor decision making with š›½-value was 0.226, with t-statistics value was 3.669 corresponding to p-value ā‰¤ 0.01.…”
Section: Discussionsupporting
confidence: 59%
“…Next, the seventh hypothesis (H7) is also confirmed and accepted, showing that overconfidence influences investor decision making with š›½-value was 0.228, with t-statistics value was 3.629 corresponding to p-value ā‰¤ 0.01. Related previous research also found that overconfident investors increase their investment ambitiously [84]. After that, the eighth hypothesis (H8) is also confirmed and accepted, showing that anchoring influences investor decision making with š›½-value was 0.226, with t-statistics value was 3.669 corresponding to p-value ā‰¤ 0.01.…”
Section: Discussionsupporting
confidence: 59%
“…We adopted Mayfield et al's (2008) scale and selected three items of short-term investment and four items of long-term investment decisions. Researchers have empirically validated this scale in several countries, including Pakistan (Ahmad, 2021;Chaudary, 2019;Jhandir and Elahi, 2014) composite reliability for short-term (0.773) and long-term investments (0.823). We employed a five-point Likert-type scale with disagree strongly (1), disagree (2), neutral (3), agree (4) and agree strongly (5) as scale anchors.…”
Section: Methodsmentioning
confidence: 99%
“…A short-term horizon signifies investors' short-term earnings; a long-term horizon represents investors' interests in long-term value (Bushee, 1998;Jhandir and Elahi, 2014;Mayfield et al, 2008). A long-term investment represents investors who hold multiple asset classes for more than one year (inaccessible for several years).…”
Section: The Love Of Money and Investment Decisions In The Emerging M...mentioning
confidence: 99%
“…Overconfidence merupakan sikap mental yang umumnya bertentangan dengan konsep keuangan dimana investor akan mengabaikan risiko tinggi yang mungkin akan ditemui karena merasa bahwa kemampuan yang dimilikinya lebih baik dibandingkan yang lain dalam memprediksi perkembangan sekuritas yang akan diambil, sehingga biasanya mereka tidak mendiversifikasikan portofolio (Khalid et al, 2018). Overconfidence dapat menimbulkan dampak pada psikologis investor ketika investasi yang diambil mengalami kerugian besar, akibat terlalu percaya diri dan nekat membeli investasi yang berisiko (Addinpujoartanto dan Darmawan, 2020).…”
Section: Overconfidenceunclassified
“…Overconfidence menyebabkan investor bertindak nekat dalam mengambil keputusan investasi karena terlalu percaya diri terhadap kemampuan penilaian mereka pada suatu investasi, tentu hal ini berdampak pada psikologis mereka jika investasi tersebut gagal (Addinpujoartanto dan Darmawan, 2020). Biasanya investor yang bersikap overconfidence akan lebih agresif dalam bertindak mengambil keputusan dan tidak ada atau cenderung sedikit diversivikasi pada portofolio mereka (Khalid et al, 2018). Overconfidence menyebabkan investor menjadi overestimate terhadap kemampuan mereka tanpa memikirkan besarnya risiko yang akan didapat (Pradikasari dan Isbanah, 2018).…”
Section: Pengaruh Overconfidence Terhadap Keputusan Investasi Cryptoc...unclassified